PENILE AMPUTATION DUE TO IMPROVISED EXPLOSIVE DEVICE (IED) BLAST INJURY IN A PAKISTANI SOLDIER: Penile Amputation - Ayaz, Saeed Bin; Gill, Zaheer Ahmed; Khan, Atif Ahmed; Butt, Amir Waheed (Pakistan Armed Forces Medical Journal, 2014)
Penile amputation is a catastrophe and the goal should be to restore adequate mass, sensation and functionality of penis considering penile prosthesis where necessary. A case of a 25 year soldier who had penile amputation due to improvised explosive device blast injury is reported.